THE ROLE OF FOREIGN DIRECT INVESTMENT IN THE ORGANIZATION AND DEVELOPMENT OF AN INNOVATION CLUSTER - Khoshimov Sabir Murtazaevich; Ganiev Shahiriddin Vohidovich (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
The article examines the organization and development of innovation clusters in the system of international economic relations of countries, the role and importance of clusters in the economic development of countries, and discusses conclusions and recommendations based on international experience.